Opção pelos pobres no Teatro de Augusto Boal: múltiplos caminhos para o conhecimento de Deus - Narcizo, David Bruno (2023)
The main objective of this research is to first present the relationship between theater and religion, however, this work does not have literature as an element, but the dramatic phenomenon itself and the religious phenomenon, that is, it brings as its main element the theatrical spectacle together with the construction of the group, the director, the actor, the director and the playwright within a historical context. Thus, it relates these elements with the religious cult, its myths and the elements that make up the religious phenomenon. In a second moment, this research observes the brazilian theater and the theater of Augusto Boal and seeks to find there elements that present a direct relationship with religion, mainly the Christian one and for that, it establishes that the primordial element for this religious aspect is the preferential option for the poor and the guarantee of the dignity of the human person, thus making a research that focuses primarily on theological anthropology that we can also find in artistic manifestations that are not exactly with narratives that speak of God, but reveal the Judeo-Christian divinity in its creation core. The methodology used was to look for works by three aspects, firstly those dealing with the history of theater and presenting its relationship with religion, for that we made use of the works of Fernando Peixoto, Sábato Magaldi and Margot Berthold, thus, we were able to trace a path from the primitive theater to the modern theater, presenting all the relationship that it has with the religious phenomenon. Secondly, we observe the works of theologians who present a relationship between art and religion and for that, we use the works of Paul Tillich and Karl Barth and also, in the science of religion, we use the works of Mircea Eliade and Marcial Maçaneiro to present the religious phenomenon from antiquity and to draw similarities with the theatrical phenomenon from the primitive theater, ancient theater and its relationship with religion. Finally, we make use of works by researchers who look at Boal's theater such as Ana Lucero Trancoso, Flávio da Conceição and, of course, the work of Augusto Boal. As a result, we were able to see the relationships that religion has with theater and, of course, we paved the way for research possibilities in ancient theater, Egyptian theater and a new look at medieval theater beyond simply talking about God, but revealing the Jewish-Christian divinity within the relationship in a group that reverberates in artistic productions that value the dignity of the human person. The great contribution of this research lies in the fact that it is, as far as we can see, the first research in theology that observes the theatrical phenomenon and, among the various researches in art, the first that observes it from a theological point of view